Penerapan Pembelajaran Kooperatif Tipe Jigsaw Berbasis Online Lerning untuk Meningkatkan Hasil Belajar Nahwu : Kooperatip Learning berbasis Online - Anwar, Khairil; Muhammad Zaky Sya'bani (An Naba, 2020)
This research is not only back grounded by the difficulty of students in understanding the rules of grammatical of Arabic language, but also pay attention to government circulars related to distance learning or in the Network so many schools have to implement Online Learning-based learning in each of their subjects Based on that background, researchers are interested in applying learning with jigsaw types. Based on Online Learning on the learning of grammatical of Arabic language rules the students' understanding of the grammatical of Arabic language rules increased. The purpose of this study is to know the application of cooperative learning with jigsaw types based on Online Learning in understanding the grammatical of Arabic language rules. The subjects of this study were grade VIII D students of 28 students. And this research was conducted in 3 cycles. Based on the results of student evaluation tests in cycle 1, cycle 2 and cycle 3 can be concluded that the application of learning with jigsaw type is quite instrumental in improving students' understanding of grammatical of Arabic language rules because the average value of all aspects of grammatical of Arabic language understanding taught has increased The average test score of all aspects of the pretest was 5.19 and then rose to 9.08 on cycle 1 tests, rising to 9.46 and on cycle 2 and rising to 10.15. Thus the average overall value of aspects from pretest to cycle 1 tests increased by 3.89% and from cycle 1 tests to cycle 2 tests increased by 0.38% and from cycle 2 tests to cycle 3 tests increased by 0.69%.